Nuevos taxa de helechos arborescentes (Filicales: Cyatheaceae) en Costa Rica - Rojas Alvarado, Alexander Francisco (2015)
New species are described and new combinations are made in the fern genera Cnemidaria and Cyathea from Costa Rica. Cnemidaria chiricana (Maxon) A. Rojas is considered here a species different from C. mutica (H. Christ) R.M. Tryon, and C. mutica var. contigua (Maxon) Stolze is included as a variety of the former. Cyathea povedae A. Rojas is here described as a new species and compared to C. fulva (M. Martens & Galeotti) Fée. The hybrid between Cyathea stolzei A.R. Sm. ex Lellinger and C. ursina (Maxon) Lellinger mentioned by Smith & Grayum (1988) is here described.